Perlindungan Hukum atas Hak-hak Nasabah terhadap Bank yang Dinyatakan Pailit - Mushafi Miftah; Laila Nofita Anggraini (Lembaga Yasin AlSys, 2025)
The limited scope of studies on legal protection for bank customers' rights in bankruptcy cases has become a significant concern, as it directly affects public trust and the stability of the national banking system. This study aims to analyze the forms of legal protection afforded to the rights of bank customers in the event of bankruptcy, based on Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. A normative legal research method was employed, using a statutory approach and analysis of primary and secondary legal materials through literature review. The findings indicate that although depositors’ rights have been accommodated through various regulations, including the role of the Indonesia Deposit Insurance Corporation (Lembaga Penjamin Simpanan, LPS), Article 2 paragraph (3) of Law No. 37 of 2004 restricts customers’ rights to file for bankruptcy against banks. This restriction is considered to conflict with the principles of justice and creditor protection, and it does not align with the principle of balance in bankruptcy law. Moreover, the resolution of banking issues tends to favor liquidation mechanisms over bankruptcy proceedings. The implications of this study include a theoretical contribution to the body of banking law literature and practical recommendations for the government and relevant authorities (Bank Indonesia, the Financial Services Authority, and LPS) to review existing regulations in order to strengthen legal protection for customers. This research also opens avenues for further studies on alternative dispute resolution mechanisms and international comparative analyses of customer protection in bank bankruptcies.